2002
DOI: 10.1002/ijc.10306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transforming growth factor‐β1 and tumour necrosis factor‐α on cultured fibroblasts from skin fibroma as modulated by toremifene

Abstract: To determine how toremifene, an anti-oestrogen triphenylethylene derivate, reduces tumour mass, we investigated its modulation of TGF-␤1 and TNF-␣ in fibroma fibroblasts. Normal and fibroma fibroblasts, isolated from patients affected by Gardner's syndrome without or with fibroma manifestation, were cultured in vitro. Secretion of GAG, collagen and TGF-␤1 was increased in fibroma fibroblasts compared to healthy cells. The increase in TGF-␤1 secretion into the medium was associated with a parallel increase in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 80 publications
0
14
0
Order By: Relevance
“…TGFß1 stimulates fibroblast proliferation [19] and Van Vlasselaer et al [20] have reported that IL-10 inhibits TGFß1 synthesis in mouse bone marrow cells. In our study, the concentration of TGFß1 in cell culture supernatants incubated with TNF· alone was almost 2.5-fold higher than that in supernatants from cells incubated with both IL-10 and TNF·, suggesting that IL-10 reduced TNF·-induced fibroblast proliferation by decreasing TGFß1 production.…”
Section: Discussionmentioning
confidence: 99%
“…TGFß1 stimulates fibroblast proliferation [19] and Van Vlasselaer et al [20] have reported that IL-10 inhibits TGFß1 synthesis in mouse bone marrow cells. In our study, the concentration of TGFß1 in cell culture supernatants incubated with TNF· alone was almost 2.5-fold higher than that in supernatants from cells incubated with both IL-10 and TNF·, suggesting that IL-10 reduced TNF·-induced fibroblast proliferation by decreasing TGFß1 production.…”
Section: Discussionmentioning
confidence: 99%
“…The fibroblastoid morphotype is associated with nuclear β-catenin and decreased E-cadherin protein expression. Interestingly, myofibroblasts isolated from desmoid tumours, which are locally invasive soft tissue tumours in which β-catenin-mediated TCF-dependent transcription is activated [114], show increased TGF-β production in comparison with fibroblasts from normal fascia [115]. This suggests a possible cooperation between Wnt/β-catenin and TGF-β signalling making desmoid myofibroblasts invasive.…”
Section: Tgf-β Stimulates Angiogenesis In Vitro and In Vivomentioning
confidence: 99%
“…Small organic molecules that fine-tune TGF-β production and activation offer another therapeutic strategy. Such molecules are Tranilast [237,238], Pirfenidone [239], Pentoxifylline [240], Toremifene [115], angiotensin-converting enzyme inhibitors [241], and Triptolide and derivatives [242]. MMP inhibitors might also have an effect on TGF-β activation.…”
Section: The Stroma: a Target For Cancer Therapymentioning
confidence: 99%
“…The loss of integrity of PGs reflects the sustained increase in parenchymal stresses, the weakening of the non-covalent bonds due to increased water binding, and the activation of tissue metalloproteases (32 Miserocchi et al, 2001a). The hypothesis that the activation of tissue metalloproteases leads to the loss of integrity of PGs faces to new therapeutic approachs by drugs able to control this family of proteinases [33,34,35].…”
Section: The Pathogenesis Of Extra Vascular Lung Water (Evlw) and Pulmentioning
confidence: 99%